Knowledge and attitudes of people living with HIV/AIDS on antiretro-viral therapy at Chizvirizvi clinic - Mhaka, Munyaradzi M. (Midlands State University, 2017)
The study sought to explore and describe knowledge and attitudes of people living with HIV/AIDS on ART. The research was driven by the realization that people living with HIV/AIDS in Chizvirizvi shown some observable signs of insufficiency of awareness like ART default which includes taking medication for a certain period of time and stopping when they feel fit and healthier and refusal to go on medication. The data was gathered through using descriptive research design, wherein self-administered questionnaires that contained items on knowledge, attitudes and adherence to the achievement of ART goals. The sample size for the case study consists of 60 male and female people living with HIV /AIDS who were randomly selected. Data presentation was done descriptively, with diagrams used as significantly as possible. The data was analysed by the application of descriptive statistics using SPSS version 16.0. The findings showed that PLWHA have knowledge on ART, however, their culture which believes in tradition affects their attitudes which results in non-adherence to medication. Having recognised the knowledge and attitudes, the researcher recommended that, a concentrated effort should be directed towards persons on ART, as part of the orientation of people on enrolment in the role out programme for ARV’s to highlight misconceptions of what ARV’s can and cannot do.